1977
DOI: 10.2343/geochemj.11.207
|View full text |Cite
|
Sign up to set email alerts
|

Cape York: The extraordinary mineralogy of an ordinary iron meteorite and its implication for the genesis of III AB irons.

Abstract: A study of accessory minerals in the Cape York iron meteorite has been carried out with the electron microprobe. Phases analyzed include chromite, sphalerite, two closely related potassium-bearing sulfides, silica, and native copper. In addition, four phosphate minerals were found: One chemically similar to buchwaldite, but rather rich in iron, one corresponding to terrestrial maricite, and two more, which seem to be new minerals on the basis of microprobe analysis. Evidence from the composition of accessory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

1979
1979
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 23 publications
0
20
0
2
Order By: Relevance
“…Anhydrous Fe,Mn,Na, Ca,Mg,K,Cr phospates are reported as small spherules (2-8 µm in diameter) within the metal-troilite inclusions of the severely shocked Yanzhuang (H6) chondrite (Chen and Xie 1996); in addition, these phases may occur in magmatic iron meteorites, particularly IIIAB irons, where they are often found in association with troilite and nearly stoichiometric FeCr 2 O 4 spinel (Kracher et al 1977;Olsen et al 1999). Very small (5-20 µm) particles of metallic Cu occur, with a frequency of ~0.1 per mm 2 , within troilite or at the metaltroilite interface (Fig.…”
Section: Texture and Mineral Chemistrymentioning
confidence: 99%
“…Anhydrous Fe,Mn,Na, Ca,Mg,K,Cr phospates are reported as small spherules (2-8 µm in diameter) within the metal-troilite inclusions of the severely shocked Yanzhuang (H6) chondrite (Chen and Xie 1996); in addition, these phases may occur in magmatic iron meteorites, particularly IIIAB irons, where they are often found in association with troilite and nearly stoichiometric FeCr 2 O 4 spinel (Kracher et al 1977;Olsen et al 1999). Very small (5-20 µm) particles of metallic Cu occur, with a frequency of ~0.1 per mm 2 , within troilite or at the metaltroilite interface (Fig.…”
Section: Texture and Mineral Chemistrymentioning
confidence: 99%
“…Ga, Ge), a similar redox state, and exposure ages indicating a major collision at -6.5 x Io 8 yr. Detailed study of the huge Cape York iron revealed many trace minerals (Kracher et at., 1977): four Nabearing phosphates (including buchwaldite NaCaPO4), six sulphides (daubr6elite, chalcopyrrhotine, djerfisherite, another K-rich sulphide, sphalerite, Fe-alabandine), chromite, copper, carlsbergite (CrN), and a silica mineral. The main group of pallasites (next section) is chemically related to the high-Ni IIIAB irons (Scott,I977a ,c).…”
Section: Forsterite-bearing Meteorites and Silicate Inclusions In Ironsmentioning
confidence: 99%
“…llAB irons are medium octahedrites, often heavily shocked (Buchwald, 1975;Steffler ef al., 1988), and have uniform exposure ages and cooling rates. They have the by far highest abundance of phosphates, suggesting formation from relatively oxidized material (Kracher et al, 1977;Olsen and Fredriksson, 1966;Olsen ef al., 1999). Silicate inclusions are documented in only two members Kracher et al, 1977;Olsen et al, 1996).…”
Section: 1222 Group Iiiar Iron Meteoritesmentioning
confidence: 99%
“…They have the by far highest abundance of phosphates, suggesting formation from relatively oxidized material (Kracher et al, 1977;Olsen and Fredriksson, 1966;Olsen ef al., 1999). Silicate inclusions are documented in only two members Kracher et al, 1977;Olsen et al, 1996). Observed compositional trends can be broadly matched by numerical models for fractional crystallization of a common core U1ff-M0I1er, 1998;Chabot and Drake, 1999;Wasson, 1999;Chabot and Drake, 2000).…”
Section: 1222 Group Iiiar Iron Meteoritesmentioning
confidence: 99%